Image Classification For Visitors Home Security - et. al., K.B Sri Sathya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The actual need of the today’s organizations and residential areas is security frameworks. The security methods which were implemented on those areas are now frequently facing major issues like break-in burglar easily. And also, the major obstacle with home security is people who are being incautious about the visitors or intruders before opening the door while security alarm goes off unfortunately. As a result, to attain the desired security, there will be an additional need of particularly skilled personnel to increase the level of safety frameworks. As a human being, those personnel will likely make faults which leads to uncertainty of persons entering into the residential zones. The main motive of the project is to provide the better home security against potential harm made by intruders and unknown visitors by recognizing them with predictable accuracy. This security system consists of hardware part and software part. The image capturing is done by camera which comes under hardware part, whereas face detection, face recognition and voice notification are all will be done based on algorithms under software part.